Pengembangan Aplikasi Adhiya Ullami Versi NWDI Berbasis Android - Rasyid Hardi Wirasasmita; Muhamamad Zamroni Uska; Syayid Khaliqussani Qushay Al Idrus; Usuluddin Usuluddin; Zaotul Wardi (Fakultas Teknik Universitas Hamzanwadi, 2023)
Madrasah Nahdlatul Wathan Diniyah Islamiyah (NWDI) is a forum for the national movement for youth, especially in the field of education. In addition to education, NWDI has a practice or prayer compiled by TGKH. Muhammad Zainuddin Abdul Majid, i.e. hizib NW. In addition to NW hizib, there are also sholawat readings that are still read by the NWDI community, especially among NWDI mahad such as al-barzanji and adhiya ullami. Adhiya ullami is also a practice of NWDI citizens which is read every Friday night, usually NWDI residents read adhiya ullami as serakal. Serakal or serakalan is a traditional Islamic religious ritual that combines verses in praise of Allah and His Messenger. The media used to learn the NWDI version of Sholawat Adhiya Ullami still uses media in the form of books or print media. The number of books is still limited so that not all people have the book, especially for beginners who still do not understand reading and have adhiya ullami books so it is difficult to learn. The objectives of this study are 1) Designing a complete, easy-to-understand and quality android-based adhiya ullami application as a source for sholawat readings for NWDI residents, 2) Knowing the feasibility results of the adhiya ullami application by experts and 3) Knowing user responses to the adhiya ullami application for NWDI residents. ADDIE model research methodology with stages of analysis, design, development, implementation and evaluation. The stages of research carried out until the implementation stage with limited-scale trials. The data collection technique uses questionnaires addressed to Media experts, Media experts and 30 people as user responses. The data analysis technique used is quantitative descriptive. The result of this study is the NWDI Version of the Adhiya Ullami Application. The results of the material expert test obtained a value of 93.5% (very feasible), the media expert test obtained a value of 93.5% (very feasible), and the results of user responses obtained a value of 90.5% (very high). Thus, it can be concluded that this application is feasible to use and has a high response as a medium for reading sholawat adhiya ullami by NWDI residents.